Trapping mode dipolar DC collisional activation in the RF‐only ion guide of a linear ion trap/time‐of‐flight instrument for gaseous bio‐ion declustering. (30th August 2013) - Webb, Ian K.; Gao, Yang; Londry, Frank A.; McLuckey, Scott A.
Abstract : The application of dipolar direct current (DDC) to the radio frequency‐only ion guide (Q0) of a hybrid quadrupole/time‐of‐flight mass spectrometer for collision‐induced declustering of large bio‐ions is described. As a broadband technique, ion trap DDC collisional activation (CA) is employed to decluster ions simultaneously over a relatively broad mass‐to‐charge ( m / z ) range. Declustering DDC CA can yield significantly narrower peaks relative to those observed in the absence of declustering methods, depending upon the extent of noncovalent adduction associated with the ions, and can also be used in conjunction with other methods, such as nozzle–skimmer CA. The key experimental variables in the DDC experiment are the DDC voltage ( V DDC ), V RF, and the time over which V DDC is applied. The V DDC / V RF ratio is key to the extent to which ion temperatures are elevated and also influences the upper m / z limit for ion storage. The V DDC / V RF ratio affects ion temperatures and the upper m / z limit in opposing directions. That is, as the ratio increases, the ion temperature also increases, whereas the upper m / z storage limit decreases. However, for a given V DDC / V RF ratio, the upper m / z storage limit can be increased by increasing V RF, at the expense of the lower m / z limit for ion storage. The key value of the approach is that it affords a relatively precise degree of control over ion temperatures as well as the time over which they are elevated to a higher temperature. The utility of the method is illustrated by the application of ion trap DDC CA in Q0 to oligonucleotide, protein, and multimeric protein complex analyte ions. Copyright © 2013 John Wiley & Sons, Ltd.